2004
DOI: 10.1007/s00423-004-0510-y
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase expression and prognosis of patients with gastrointestinal cancers receiving adjuvant chemotherapy: a review

Abstract: Patients with gastrointestinal cancers that express high TS levels have a poor prognosis with regard to fluoropyrimidine-based palliative chemotherapy or complete primary tumour resection. In contrast, patients with high TS levels might benefit from adjuvant fluoropyrimidine-based treatment after primary tumour resection. However, additional prospective studies are mandatory to define the precise role of TS in adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…For adjuvant treatment, it is controversial whether TS levels measured in primary CRC predict clinical benefit from 5-FU-based treatment. In several studies, a high TS level was associated with poor postoperative outcome, independent of the Duke's stage (Kralovánszky et al, 2002;Formentini et al, 2004), and leading to poor DFS and OS in an adjuvant setting (Cascinu et al, 2001;Kralovánszky et al, 2002;Allegra et al, 2003;Popat et al, 2004;Broll et al, 2005). In contrast, other reports indicated that high TS is predictive of 5-FU treatment and patients with a high TS level may benefit from adjuvant 5-FU therapy (Edler et al, 2002;Kornmann et al, 2003).…”
Section: Discussionmentioning
confidence: 84%
“…For adjuvant treatment, it is controversial whether TS levels measured in primary CRC predict clinical benefit from 5-FU-based treatment. In several studies, a high TS level was associated with poor postoperative outcome, independent of the Duke's stage (Kralovánszky et al, 2002;Formentini et al, 2004), and leading to poor DFS and OS in an adjuvant setting (Cascinu et al, 2001;Kralovánszky et al, 2002;Allegra et al, 2003;Popat et al, 2004;Broll et al, 2005). In contrast, other reports indicated that high TS is predictive of 5-FU treatment and patients with a high TS level may benefit from adjuvant 5-FU therapy (Edler et al, 2002;Kornmann et al, 2003).…”
Section: Discussionmentioning
confidence: 84%
“…In fact, several studies have reported a significant association between TS expression and survival in cancer patients who underwent curative resection without receiving chemotherapy. Formentini et al [40] demonstrated that high TS expression was associated with poor prognosis in patients with gastrointestinal cancer who underwent complete tumor resection but without adjuvant chemotherapy. In the current study, we found that patients with high intratumoral TS expression had a significantly worse prognosis than patients with low TS expression and that intratumoral TS expression was an independent prognostic factor in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with low TS expression given adjuvant therapy appear to have a worse prognosis than with surgery alone [81]. This appears to be different from the situation in palliative 5-FU-based chemotherapy [82]. Patients with colon tumors exhibiting high-frequency microsatellite instability do not benefit from 5-FU-based chemotherapy [4].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%